Clinical course and disease outcomes in hospitalized patients with 2019 novel corona virus disease at Ibn- Al Khateeb Hospital in Baghdad, Iraq - Mohammed, Iman Ahmed; Ali, Abbas Hasan; Al shenaty, Jaafer Naseer (Journal of the Faculty of Medicine Baghdad, 2020)
Background: the novel coronavirus (2019-ncov), formally known as severe acute respiratory syndrome coronavirus 2 (sars-cov-2), the etiological cause of the (corona virus disease 2019) covid-19, appeared in wuhan, hubei province, china. On 11 march 2020, the world health organization (who) declared this disease as a pandemic. As new information on the clinical characteristics, treatment options, and outcomes for covid-19 emerges approximately every hour, physicians should keep themselves up-to-date on this topic. Objective: to study the demographic features, clinical signs and symptoms and certain vital and laboratory findings of covid-19 hospitalized cases; and to identify the used medication, complications, length of stay at the hospital and disease outcomes of confirmed covid-19 cases. Patients and methods: a descriptive cross-sectional study with analytic elements was conducted at ibn-al khateeb hospital, baghdad on covid-19 patients admitted to the hospital from 1st of march to 4th of may 2020. All inpatients of all age groups, diagnosed as covid-19 and had a definite outcome (recovered and discharge or death) during the period of the study were included. Results: the mean age ± sd for the patients included in the study was = 37.9±18.85 years, with 51.2% being males. The outcome was statistically significantly associated with age, marital status, hypertension, disease severity at admission and length of stay at hospital. Conclusion: this study found that age was associated with disease outcome. Care, attention and monitoring should be taken into consideration for hypertensive patients. Patients’ initial signs and symptoms of dyspnea, weakness and sore throat were significantly associated with disease outcome.